2014
DOI: 10.1017/s0263574714001568
|View full text |Cite
|
Sign up to set email alerts
|

The effects on biomechanics of walking and balance recovery in a novel pelvis exoskeleton during zero-torque control

Abstract: 2014). The effects on biomechanics of walking and balance recovery in a novel pelvis exoskeleton during SUMMARY Fall-related accidents are among the most serious concerns in elderly people, amputees and subjects with neurological disorders. The aim of this paper was to investigate the behaviour of healthy subjects wearing a novel light-weight pelvis exoskeleton controlled in zero-torque mode while carrying out unperturbed locomotion and managing unexpected perturbations. Results showed that the proposed exoske… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 33 publications
(46 reference statements)
2
22
0
Order By: Relevance
“…3A and B, respectively, grey curves2425). Thus, the exoskeleton appeared likely transparent while participants walked steadily, confirming previous results26.…”
Section: Resultssupporting
confidence: 89%
“…3A and B, respectively, grey curves2425). Thus, the exoskeleton appeared likely transparent while participants walked steadily, confirming previous results26.…”
Section: Resultssupporting
confidence: 89%
“…Previous studies [13], [14], [15], [16] have investigated some aspects of balance with a robotic exoskeleton using testing with a single subject and the study [17] investigated assisted balance recovery following slippage in walking with eight elderly participants. In this context, this paper has presented the first study which systematically analyses balance recovery in standing through stepping with a robotic exoskeleton on four subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In [11], [12] a lower limb exoskeleton with variable stiffness actuators was used for balance recovery, however experiments were performed with the robot only. In [13] the influence of passive exoskeleton mechanics on human biomechanics of walking and balancing was investigated. It was shown that a passive exoskeleton degraded the balancing performance when perturbations were applied to the exoskeleton's user.…”
Section: A State Of the Artmentioning
confidence: 99%
See 1 more Smart Citation
“…and to minimize the extent to which the exoskeleton robot might hinder a pilot's movements. Martelli et al [120] developed a zerotorque cascade controller with a 2-pole 2-zero control loop outside a velocity control loop. The controller was used in a pelvis exoskeleton robot to investigate the behaviour of healthy pilots when wearing it.…”
Section: Interaction Force-based Torque Assistmentioning
confidence: 99%